Mortality predictors and early outcomes in very low birth weight infants: A retrospective cross-sectional study. - Abbas, Zahir; Ahmad, Ghazi Sharique (Student's Journal of Health Research Africa, 2025)
Background: Very low birth weight (VLBW) infants, defined as those weighing under 1500 g, are highly vulnerable to morbidity and mortality, particularly in low-resource settings. Despite advances in neonatal care, outcomes remain inconsistent, with respiratory distress syndrome (RDS), sepsis, and prematurity as major contributors to mortality. Aim: To evaluate short-term outcomes and identify mortality predictors among VLBW infants admitted to the NICU of Katihar Medical College, Bihar. Methods: This retrospective descriptive cross-sectional study was conducted over one year (November 2023–October 2024) and included 60 VLBW infants. Data on demographic characteristics, perinatal factors, complications, and outcomes were collected from hospital records and analyzed using SPSS version 23.0. The Chi-square and t-tests were used for univariate analysis, and logistic regression identified independent predictors of mortality. Results: The mean birth weight and gestational age were 1225 ± 180 g and 30.8 ± 2.4 weeks, respectively. Survival was achieved in 42 infants (70%), while 18 (30%) died during NICU stay. Mortality was higher among infants with birth weight <1000 g (66.7%), gestational age <32 weeks (38.9%), RDS (47.4%), and sepsis (54.5%) (p<0.05). Logistic regression identified birth weight <1000 g (OR 4.3; p=0.007), RDS (OR 3.9; p=0.012), and sepsis (OR 3.1; p=0.031) as independent mortality predictors. Conclusion: Extremely low birth weight, respiratory distress syndrome, and sepsis are key determinants of mortality among VLBW infants. Early recognition and targeted management of these risk factors, along with strengthened neonatal intensive care services, are essential to improve survival outcomes. Recommendations: Early identification of risk factors, timely surfactant therapy, strict infection control, and improved NICU infrastructure can help reduce mortality in VLBW infants.